2007
DOI: 10.1111/j.1600-0714.2007.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral premalignant lesions: is a biopsy reliable?

Abstract: The estimated odds ratio showed that none of the associated variables including presence of any degree of epithelial dysplasia in the whole lesion, site, demarcation and smoking had influence on the risk of malignant development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 27 publications
4
104
0
10
Order By: Relevance
“…We thus believe that the histopathological diagnosis reflects the true nature of the lesion. Holmstrup et al (19), in a retrospective study to learn whether an incisional biopsy of oral premalignant lesions, leukoplakia and erythroplakia, showed histopathological findings representative of the whole surgically removed lesion, observed underdiagnosis in 35% of the incisional biopsies, and stepwise sectioning revealed seven unexpected carcinomas (7%).…”
Section: Discussionmentioning
confidence: 99%
“…We thus believe that the histopathological diagnosis reflects the true nature of the lesion. Holmstrup et al (19), in a retrospective study to learn whether an incisional biopsy of oral premalignant lesions, leukoplakia and erythroplakia, showed histopathological findings representative of the whole surgically removed lesion, observed underdiagnosis in 35% of the incisional biopsies, and stepwise sectioning revealed seven unexpected carcinomas (7%).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that presence of Oral Epithelial Dysplasia (OED) in OPML as the most reliable factors predicting malignant transformation (Abbey et al, 1995). But there are other studies contradicting the presence of epithelial dysplasia in the biopsy not being a significant factor for malignant development (Holmstrup et al, 2007). Histopathological assessment many times is subjected to inter-observer variation.…”
Section: Introductionmentioning
confidence: 99%
“…Dans l'étude prospective, toutes les lésions ont bénéficié d'une analyse anatomopathologique à partir de biopsies réalisées avant la première consultation ou lors de celle-ci. Certains auteurs ont souligné que, concernant les lésions « pré-cancéreuses » de la muqueuse buccale, la biopsie localisée était insuffisante et que l'exérèse complète de la lésion et son étude anatomopathologique était nécessaire pour évaluer la présence et le grade de la dysplasie [15] . Ainsi, dans une étude portant sur 101 lésions « pré-cancéreuses » ou précurseurs du carcinome épi-dermoïde chez 96 patients, Holmstrup et coll.…”
Section: Biopsieunclassified
“…Ainsi, dans une étude portant sur 101 lésions « pré-cancéreuses » ou précurseurs du carcinome épi-dermoïde chez 96 patients, Holmstrup et coll. ont comparé les données histologiques de l'exérèse totale de la lésion réalisée en moyenne 10,4 mois après la biopsie [15] . Les résultats de l'étude montraient que 35 % des lésions avaient un degré de dysplasie plus sévère sur un endroit de la lésion qui n'a pas été intéressé par la biopsie initiale.…”
Section: Biopsieunclassified